Semantic Shifts in Hellenistic Greek: ἀνάτασις and παράστασις - Cerroni, Enrico (Hyperboreus, 2020)
This study aims to evaluate the possibility of applying the subjectiﬁcation theory to the diachronic semantics of Hellenistic Greek and it does so starting from two examples: ἀνάτασις and παράστασις. For both words, an original polysemy is observed, particularly accentuated in the second case since Homer: in fact, it is essential to ‘stay near’ (παρίσταμαι), in order to give courage and help someone. In Hellenistic Greek the abstract corradical term παράστασις is attested with the meaning ‘impetus’, ‘courage’, which is the coherent development of a possibility already implicit several centuries before. The path of ἀνάτασις, originally ‘stretching out’, is probably less predictable, even though it can be traced back to a gesture of body language that can be found in many languages. Raising the hand, indeed, is often associated with an attitude of threat. Polybius uses the verb ἀνατείνω and the corresponding abstract noun in the meaning of ‘threat’ and ‘threatening’.